Pengaruh Model Pembelajaran Teams Games Tournament (TGT) Dengan Motivasi Belajar Siswa Pendidikan Agama Kristen Kelas VIII SMP Negeri 1 Baktiraja Tahun Pembelajaran 2023/2024 - Moreyta Hasianna Pasaribu; Rida Gultom; Nisma Simorangkir (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The aim of this research is to determine the positive and significant influence of the Teams Games Tournament (TGT) learning model on the learning motivation of class VIII PAK students at SMP Negeri 1 Baktiraja for the 2023/2024 academic year. The research method used is a quantitative inferential descriptive method. The population is all Class VIII students at SMP Negeri 1 Baktiraja for the 2023/2024 academic year with a total of 144 people and a sample of 44 people was determined using random sampling techniques. Data was collected using a positive closed questionnaire with 40 items, namely 15 items for variable 2023/2024 learning, proven through the following data analysis: 1) Test the analysis requirements: a) positive relationship test obtained by the value rxy = 0.542 > rtable(α=0.05,n=44) = 0.297. b) Testing a significant relationship obtained tcount= 4.178 > ttable(α=0.05, dk=n-2=32)= 2.021. 2) Influence test: a) Regression equation test, obtained regression equation. b) Regression coefficient of determination test (r2) = 29.4%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(α=0.05, dk numerator k=16, dk denominator=n-2=44-2=42) namely 17.44 > 1.51. Thus Ha is accepted and H0 is rejected.